2020
DOI: 10.4103/ijnm.ijnm_140_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic accuracy and impact of preoperative positron emission tomography/computed tomography in the management of early operable breast cancers

Abstract: Aim: Our aim of this study was to evaluate the diagnostic accuracy of staging positron emission tomography/computed tomography (PET/CT) in early breast cancers (EBCs) and to assess its impact on disease management. Patients and Methods: We retrospectively reviewed preoperative PET/CT scans of patients from January 2015 to December 2018 with Stage I/II, clinically T1-T2 N0-N1 breast cancers. The diagnostic performance of PET/CT for nodal (N) and distant metastases (M), its correlation with patient/tumor-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…BC is the commonest cancer and the leading cause of cancer mortality among women worldwide [1].Classification can be done according to TNM stage, immunohistochemical features, grade, proliferation index and gene expression profiles, with histopathology remaining the cornerstone of characterization [2]. Immunohistochemistry (IHC) markers such as ER, PR and Her2neu, along with clinicopathological variables including; tumor size, grade and nodal involvement are commonly used for patient prognosis and management [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…BC is the commonest cancer and the leading cause of cancer mortality among women worldwide [1].Classification can be done according to TNM stage, immunohistochemical features, grade, proliferation index and gene expression profiles, with histopathology remaining the cornerstone of characterization [2]. Immunohistochemistry (IHC) markers such as ER, PR and Her2neu, along with clinicopathological variables including; tumor size, grade and nodal involvement are commonly used for patient prognosis and management [3,4].…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 30 32 , 35 38 , 40 Twenty-five studies were regarded as having an unclear risk of bias in confounding variables because the exact time interval between conventional staging procedures and PET scans was not reported. 12 , 14 , 16 27 , 29 32 , 34 40 For the measurement of exposure domain, 6 studies had a high risk of bias because a single reader interpreted PET images, 13 , 15 , 29 , 34 , 37 , 38 and 6 studies had an unclear risk of bias because they did not report the number of readers or their experience. 18 , 20 , 27 , 28 , 30 , 39 Regarding the blinding of outcome assessments domain, 13 studies had an unclear risk of bias as it was unclear whether PET interpretation was performed in a blinded manner, 15 , 16 , 18 , 22 24 , 28 30 , 32 , 35 , 36 , 40 and 1 study had a high risk of bias because PET interpretation was not blinded to the findings of other tests.…”
Section: Resultsmentioning
confidence: 99%
“… 18 , 20 , 27 , 28 , 30 , 39 Regarding the blinding of outcome assessments domain, 13 studies had an unclear risk of bias as it was unclear whether PET interpretation was performed in a blinded manner, 15 , 16 , 18 , 22 24 , 28 30 , 32 , 35 , 36 , 40 and 1 study had a high risk of bias because PET interpretation was not blinded to the findings of other tests. 19 For outcome evaluation, 10 studies showed an unclear risk of bias as the method for classifying stage was not explicitly mentioned, 12 , 14 , 17 , 25 , 27 , 28 , 30 32 , 36 and 2 studies had a high risk of bias as the method for confirmation of additional lesions on PET scan was reported. 24 , 39 …”
Section: Resultsmentioning
confidence: 99%
“…18 FDG PET/CT could be used to determine whether patients require SNB or ALND (10,18), thereby avoiding a potentially unnecessary invasive procedure (10,14). Some authors suggest that when 18 FDG PET/CT is positive patients could be offered ALND immediately (8,28,32), whereas a negative finding on 18 FDG PET/CT indicates the continued need of SNB. This is due to the high FN rate observed (8).…”
Section: Discussionmentioning
confidence: 99%